The effect of Cornus mas fruit extract on vasomotor symptoms and sex hormones in postmenopausal women: a randomized, double-blind, clinical trial. Issue 2 (13th February 2023) - Rimaz, Shahnaz; Rahideh, Seyedeh Tayebeh; Abolghasemi, Jamileh; Jazayeri, Shima; Jamshidi, Sanaz; Motevalian, Manijeh; Solaymani-Dodaran, Masoud; Taghizadeh, Mohsen; Gholamrezayi, Afsaneh; Aryaeian, Naheed
Abstract : This study found that the extract of Cornus mas fruit has a favorable effect on vasomotor manifestations, sex hormones, and related complications in women experiencing menopausal symptoms. Abstract: Objectives: Cornus mas fruit has various antioxidants and anti-inflammatory properties, so this study aims at assessing its effect on menopausal symptoms and sex hormones in postmenopausal women. Methods: In the current randomized, double-blind clinical trial, 84 individuals (42 per group) were participated. C mas hydroalcoholic extract was prepared, and participants received 300 mg C mas extract or placebo three times a day (900 g in total) for 8 weeks. The demographic, dietary intake, and physical activity information were gathered. Anthropometric indices were measured by standard methods. Furthermore, menopause symptoms were assessed by Greene Climacteric Scale. Also, sex hormones were measured by enzyme-linked immunosorbent assay. Results: Based on the results, there was a significant difference in total Greene score reduction between the intervention and placebo groups (−3.19 ± 0.54, −0.76 ± 0.32, and P < 0.001). In addition, vasomotor symptoms had a remarkable decrease in the C mas extract group ( P < 0.001). Also, the intervention group demonstrated a decreasing trend in the number and duration of hot flushes. Moreover, follicle-stimulating hormone remarkably decreased and estradiol increased in the intervention group ( P = 0.016 and P = 0.018). Conclusions: It has been found that the extract of C mas fruit has a favorable effect on vasomotor symptoms, sex hormones, and related complications in women experiencing menopausal symptoms.